Challenges and accomplishments of ELT at primary level in Chile: Towards the aspiration of becoming a bilingual country - Barahona, Malba (Education Policy Analysis Archives, 2016)
This paper explores the policy development supporting the implementation of English language teaching (ELT) in Chile at primary level over the last two decades. This policy—which made English instruction compulsory for all Chilean students from fifth grade—has had to deal with a series of significant challenges since its introduction. One key impediment has been the lack of qualified teachers of English at primary school level. In addition, in a crowded curriculum, English teaching has been often allocated inadequate number of hours to facilitate successful language acquisition. Further, suitable learning resources and support materials—especially designed for young learners—have often been limited. Nevertheless, it can be argued that the broader offering of English, particularly at the primary level, has had an important democratising effect. It has been somewhat effective in allowing children from lower socioeconomic backgrounds to access a global language and a potential world of opportunities previously only available to students attending wealthy private institutions. Data suggests that this policy has had some impact in establishing educational foundations for broader access to more advanced language learning for all students in Chile. However, equally it demonstrates further resources and support for teachers and teaching is essential to realise this potential.